Surface treatment method of metal current-carrying strip

By performing plasma treatment, corona treatment or fine polishing on the surface of the metal current-carrying strip, the surface roughness is improved, and the problem of insufficient adhesion between the conductive paste and the metal current-carrying strip is solved, and the stability of electrical performance is significantly improved.

CN119685819APending Publication Date: 2025-03-25BEIJING AIKALIFE LNNOVATIVE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411856369.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, the bonding force between the conductive paste and the metal current-carrying strip is limited, resulting in the problem of degradation of conductive properties and insolid bonding.

Method used

By performing plasma treatment, corona treatment or fine polishing on the surface of the metal current-carrying strip, its surface roughness is improved, thereby enhancing the adhesion to the conductive paste.

Benefits of technology

The bonding force between the metal current-carrying strip and the conductive paste is improved, the stability of electrical properties is improved, and the bonding force is increased by more than 25%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685819A_ABST
    Figure CN119685819A_ABST
Patent Text Reader

Abstract

The invention provides a surface treatment method of a metal current-carrying strip, and belongs to the technical field of metal surface treatment. According to the invention, plasma treatment, corona treatment or fine polishing is carried out on the surface of the metal current-carrying strip, and each process parameter is controlled, so that the surface roughness of the metal current-carrying strip is improved, and the bonding force between the metal current-carrying strip and the conductive slurry is further improved. The result of the embodiment shows that after the surface treatment method is adopted for treatment, the surface roughness of the metal current-carrying strip is 0.803 microns or above, and compared with a metal current-carrying strip without surface treatment, the binding power is improved by 25% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal surface treatment, and in particular relates to a surface treatment method for a metal current-carrying bar. Background Art

[0002] With the rapid development of my country's graphene industry, graphene composites are increasingly used in the automotive industry, especially in the heating field of car seats, door panels, battery packs, floor mats and other components, showing great potential and advantages. The commonly used method is to compound graphene with polymer materials to form a conductive film, and then compound it with a metal current-carrying bar. However, the adhesion between the conductive film and the metal current-carrying bar is poor, which affects its electrical properties and stability. In order to solve this problem, the prior art uses a conductive paste to connect the conductive film to the metal current-carrying bar. However, the adhesion between the conductive paste and the metal current-carrying bar is limited, and in actual use, there will be problems such as decreased conductivity and loose bonding.

[0003] Therefore, how to improve the bonding force between the conductive paste and the metal current-carrying strip has become a difficult problem in the prior art. Summary of the invention

[0004] The object of the present invention is to provide a surface treatment method for a metal bus bar. The surface treatment method provided by the present invention can improve the surface roughness of the metal bus bar, thereby improving the bonding force between the metal bus bar and the conductive paste.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a surface treatment method for a metal current-carrying bar, comprising:

[0007] Plasma treatment, corona treatment or fine grinding is performed on the surface of the metal current-carrying bar to obtain a treated metal current-carrying bar;

[0008] The power of the plasma treatment is 10 to 300 W, the time of the plasma treatment is 0.5 to 10 min, and the gas flow rate of the plasma treatment is 10 to 100 sccm;

[0009] The voltage of the corona treatment is 5 to 15 kV, the time of the corona treatment is 5 to 60 s, and the current of the corona treatment is 10 to 50 mA;

[0010] The fine grinding includes grinding with sandpaper, grinding paste or grinding with a diamond grinding tool.

[0011] Preferably, the plasma source of the plasma treatment comprises one or more of oxygen, argon and nitrogen.

[0012] Preferably, the distance between electrodes in the corona treatment is 1 to 10 mm.

[0013] Preferably, the sandpaper polishing is performed step by step using sandpapers of different mesh sizes.

[0014] Preferably, the mesh size of the sandpaper gradually increases during sanding.

[0015] Preferably, the mesh number of the sandpaper used for sanding is 100 to 1000.

[0016] Preferably, the mesh difference between the sandpapers during sanding is 200 to 400 meshes.

[0017] Preferably, the material of the metal current-carrying bar includes copper, aluminum or nickel.

[0018] Preferably, the thickness of the metal current-carrying bar is 0.01-0.1 mm.

[0019] Preferably, the metal bus bar is cleaned and dried in sequence before use.

[0020] The present invention provides a surface treatment method for a metal current-carrying bar, comprising: performing plasma treatment, corona treatment or fine grinding on the surface of the metal current-carrying bar to obtain the treated metal current-carrying bar; the power of the plasma treatment is 10 to 300 W, the time of the plasma treatment is 1 to 10 min, and the gas flow rate of the plasma treatment is 10 to 100 sccm; the voltage of the corona treatment is 5 to 15 kV, the time of the corona treatment is 5 to 60 s, and the current of the corona treatment is 10 to 50 mA; the fine grinding includes sandpaper grinding, grinding paste grinding or diamond grinding tool grinding. The present invention performs plasma treatment, corona treatment or fine grinding on the surface of the metal current-carrying bar, and controls various process parameters, thereby improving the surface roughness of the metal current-carrying bar, and thereby improving the bonding force between the metal current-carrying bar and the conductive paste. The results of the embodiment show that after being treated by the surface treatment method of the present invention, the surface roughness of the metal current-carrying bar is above 0.803 μm, and the bonding force is increased by more than 25% compared with the metal current-carrying bar that has not been surface treated. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a SEM image of the untreated metal current-carrying bar in Example 1;

[0022] Figure 2 is the surface roughness of the untreated metal bus bar in Example 1;

[0023] Figure 3 is a SEM image of the metal current-carrying bar after treatment in Example 1;

[0024] Figure 4is the surface roughness of the metal bus bar after treatment in Example 1;

[0025] Figure 5 is a SEM image of the untreated metal current-carrying bar in Example 2;

[0026] Figure 6 is the surface roughness of the untreated metal bus bar in Example 2;

[0027] Figure 7 is a SEM image of the metal current-carrying bar after treatment in Example 2;

[0028] Figure 8 is the surface roughness of the metal bus bar after treatment in Example 2;

[0029] Fig. 9 is a SEM image of the untreated metal current-carrying bar in Example 3;

[0030] Fig.10 is the surface roughness of the untreated metal bus bar in Example 3;

[0031] Fig.11 is a SEM image of the metal current-carrying bar after treatment in Example 3;

[0032] Fig.12 is the surface roughness of the metal bus bar after treatment in Example 3. DETAILED DESCRIPTION

[0033] The present invention provides a surface treatment method for a metal current-carrying bar, comprising:

[0034] The surface of the metal bus bar is subjected to plasma treatment, corona treatment or fine grinding to obtain a treated metal bus bar.

[0035] In the present invention, the material of the metal current carrying bar preferably includes copper, aluminum or nickel. In the present invention, the metal current carrying bar is preferably used for a graphene heating sheet.

[0036] In the present invention, the thickness of the metal bus bar is preferably 0.01-0.1 mm. In an embodiment of the present invention, the thickness of the metal bus bar may be specifically 0.01 mm, 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm or 0.1 mm.

[0037] In the present invention, the metal bus bar is preferably cleaned and dried in sequence before use.

[0038] In the present invention, the cleaning preferably includes ultrasonic cleaning with an organic solvent or acid cleaning followed by water cleaning.

[0039] In the present invention, the organic solvent preferably includes ethanol or acetone. The present invention has no particular limitation on the amount of ethanol and acetone, as long as the amount can cover the metal current-carrying strip.

[0040] In the present invention, the power of the ultrasonic cleaning is preferably 100 to 500 W; the time of the ultrasonic cleaning is preferably 5 to 30 min.

[0041] In the present invention, the pickling acid preferably includes hydrochloric acid or nitric acid.

[0042] In the present invention, the mass concentration of the hydrochloric acid is preferably 0.5-8%; the mass concentration of the nitric acid is preferably 0.5-85%. The present invention has no special limitation on the amount of the acid, as long as it can cover the metal current-carrying strip.

[0043] In the present invention, the number of times of pickling is preferably 1 to 3. The present invention has no special limitation on other operations of pickling, and the technical solutions well known to those skilled in the art can be adopted.

[0044] The present invention has no special limitation on the water washing operation, and the technical solutions well known to those skilled in the art can be adopted.

[0045] The present invention cleans the metal current-carrying bar to remove oil stains, oxides and other pollutants on the surface of the metal current-carrying bar.

[0046] In the present invention, the drying temperature is preferably 60 to 120°C; the drying time is preferably 10 to 60 minutes. The present invention dries the metal current-carrying bar to avoid affecting the subsequent surface treatment. In the present invention, the drying is preferably carried out in a hot air drying device or a vacuum drying device. The present invention does not specifically limit the model of the hot air drying device or the vacuum drying device, and commercially available equipment familiar to those skilled in the art can be used.

[0047] As an embodiment, the present invention performs plasma treatment on the surface of the metal current-carrying bar to obtain the treated metal current-carrying bar.

[0048] In the present invention, the plasma source of the plasma treatment preferably includes one or more of oxygen, argon and nitrogen, more preferably oxygen, argon, nitrogen, a mixed gas of oxygen and nitrogen, or a mixed gas of oxygen and argon.

[0049] In the present invention, when the plasma source of the plasma treatment is a mixed gas of oxygen and nitrogen, the volume ratio of the oxygen and nitrogen is preferably 1:(1-2).

[0050] In the present invention, when the plasma source of the plasma treatment is a mixed gas of oxygen and argon, the volume ratio of the oxygen to argon is preferably 1:(1-3).

[0051] In the present invention, the power of the plasma treatment is 10 to 300 W. In an embodiment of the present invention, the power of the plasma treatment may specifically be 10 W, 50 W, 100 W, 150 W, 200 W, 250 W or 300 W.

[0052] In the present invention, the plasma treatment time is 0.5 to 10 minutes. In an embodiment of the present invention, the plasma treatment time can be specifically 0.5 minutes, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes.

[0053] In the present invention, the gas flow rate of the plasma treatment is 10 to 100 sccm. In an embodiment of the present invention, the gas flow rate of the plasma treatment may be specifically 10 sccm, 20 sccm, 30 sccm, 40 sccm, 50 sccm, 60 sccm, 70 sccm, 80 sccm, 90 sccm or 100 sccm. In the present invention, during the plasma treatment process, the plasma source is excited to form a plasma, and the high-energy particles in the plasma physically etch or chemically react with the metal surface, increase its surface roughness and activity, and form a surface structure that is conducive to bonding. The present invention controls the parameters of the plasma treatment within the above range, which can make the plasma have better activity, stability and uniformity, and further improve the surface treatment effect.

[0054] After the plasma treatment is completed, the present invention preferably cools the metal current-carrying bar after the plasma treatment.

[0055] In the present invention, the cooling preferably includes natural cooling or air cooling. The present invention has no special limitation on the operation of the air cooling, and the air cooling technical solution well known to those skilled in the art can be used.

[0056] In the present invention, the plasma treatment equipment is preferably a plasma cleaning machine or a plasma etcher. The present invention has no special limitation on the model of the plasma treatment equipment, and commercially available equipment well known to those skilled in the art can be used.

[0057] In the present invention, before the plasma treatment, the plasma treatment equipment is preferably evacuated to 10 -6 ~10 - 3 Torr, and then introduced into the plasma source.

[0058] As an embodiment, the present invention performs corona treatment on the surface of the metal current-carrying bar to obtain the treated metal current-carrying bar.

[0059] In the present invention, the voltage of the corona treatment is 5 to 15 kV. In an embodiment of the present invention, the voltage of the corona treatment may be specifically 5 kV, 6 kV, 7 kV, 8 kV, 9 kV, 10 kV, 11 kV, 12 kV, 13 kV, 14 kV or 15 kV.

[0060] In the present invention, the time of the corona treatment is 5 to 60 seconds. In an embodiment of the present invention, the time of the corona treatment can be specifically 5 seconds, 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds or 60 seconds.

[0061] In the present invention, the current of the corona treatment is 10-50 mA. In an embodiment of the present invention, the current of the corona treatment can be specifically 10 mA, 20 mA, 30 mA, 40 mA or 50 mA.

[0062] In the present invention, the electrode spacing of the corona treatment is preferably 1 to 10 mm. In an embodiment of the present invention, the electrode spacing of the corona treatment may be specifically 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm. In the present invention, during the corona treatment, low-temperature plasma will be generated on the surface, increasing the surface energy and roughness, thereby improving adhesion. The present invention controls the parameters of the corona treatment within the above range, which can further improve the surface roughness and adhesion of the metal current-carrying strip.

[0063] As an implementation mode, the present invention finely grinds the surface of the metal bus bar to obtain a processed metal bus bar.

[0064] In the present invention, the fine grinding includes sandpaper grinding, grinding paste grinding or diamond grinding tool grinding.

[0065] In the present invention, the sandpaper polishing is preferably performed step by step using sandpapers of different meshes; the mesh of the sandpaper during the sandpaper polishing is preferably 100 to 1000 meshes; the mesh of the sandpaper during the sandpaper polishing is preferably gradually increased; the mesh difference between the sandpapers during the sandpaper polishing is preferably 200 to 400 meshes, more preferably 300 meshes. The present invention controls the parameters during sandpaper polishing within the above range, which can further improve the surface roughness and adhesion of the metal current-carrying strip.

[0066] After the sandpaper grinding is completed, the present invention preferably polishes the metal current-carrying strip after the sandpaper grinding.

[0067] In the present invention, the polishing preferably includes polishing with a polishing paste or a polishing wheel.

[0068] In the present invention, the polishing paste is preferably an aluminum oxide polishing paste.

[0069] In the present invention, after polishing, the surface roughness of the metal bus bar is preferably 1.5-1.6 μm.

[0070] After polishing is completed, the present invention preferably cleans and dries the polished metal bus bar in sequence.

[0071] In the present invention, the cleaning solvent is preferably acetone or ethanol. The present invention has no special limitation on other cleaning operations, and the cleaning technical solutions well known to those skilled in the art can be used.

[0072] The present invention has no special limitation on the drying operation, and any drying technical solution well known to those skilled in the art may be used.

[0073] The present invention performs plasma treatment, corona treatment or fine grinding on the surface of the metal current-carrying bar and controls various process parameters, thereby improving the surface roughness of the metal current-carrying bar and further improving the bonding force between the metal current-carrying bar and the conductive paste.

[0074] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0075] Example 1

[0076] Surface treatment method of metal current-carrying bar: (1) pickling the metal current-carrying bar (made of copper and having a thickness of 0.027 mm) with nitric acid having a mass concentration of 8% for 10 min, then rinsing with distilled water and drying at 80° C. for 20 min;

[0077] (2) Place the cleaned and dried metal current-carrying strip into the plasma treatment chamber, turn on the vacuum pump, and evacuate to 10 -4 Torr, a plasma source (a mixture of oxygen and nitrogen, with a volume ratio of oxygen to nitrogen of 1:1) was introduced for plasma treatment with a power of 100 W, a time of 30 s, a gas flow rate of 30 sccm, and cooling to obtain a treated metal current-carrying strip.

[0078] The SEM image of the untreated metal current carrying strip in Example 1 is as follows: Figure 1 The measured surface roughness is shown in Figure 2 shown.

[0079] The SEM image of the metal current carrying strip after treatment in Example 1 is as follows: Figure 3 The measured surface roughness is shown in Figure 4 shown.

[0080] from Figure 2 and 4 It can be seen that the surface roughness of the untreated metal bus bar is 0.972 μm, and the surface roughness of the treated metal bus bar is 1.744 μm.

[0081] In Example 1, the surfaces of the untreated metal current-carrying bar and the treated metal current-carrying bar are coated with conductive silver paste (silver content 55wt%) and then dried to obtain a metal current-carrying bar with a surface coated with conductive paste. The adhesion is tested using a tensile testing machine. The adhesion of the untreated metal current-carrying bar in Example 1 is 84.14gf, and the adhesion of the treated metal current-carrying bar is 125.56gf, with an adhesion increase of 49%.

[0082] Example 2

[0083] Surface treatment method of metal current-carrying bar: (1) pickling the metal current-carrying bar (made of copper and having a thickness of 0.027 mm) with nitric acid having a mass concentration of 5% for 10 min, then rinsing with distilled water and drying at 80° C. for 20 min;

[0084] (2) The cleaned and dried metal current-carrying strip is placed in a corona treatment device for corona treatment. The corona treatment voltage is 10 kV, the corona treatment time is 20 s, the corona treatment current is 30 mA, and the electrode spacing of the corona treatment is 2 mm, thereby obtaining a treated metal current-carrying strip.

[0085] The SEM image of the untreated metal current carrying strip in Example 2 is as follows: Figure 5 The measured surface roughness is shown in Figure 6 shown.

[0086] The SEM image of the metal current carrying strip after treatment in Example 2 is as follows: Figure 7 The measured surface roughness is shown in Figure 8 shown.

[0087] from Figure 6 and 7 It can be seen that the surface roughness of the untreated metal bus bar is 0.515 μm, and the surface roughness of the treated metal bus bar is 0.803 μm.

[0088] The same method was used to measure the bonding force of the untreated metal bus bar in Example 2 to be 77.25 gf, and the bonding force of the treated metal bus bar to be 96.56 gf, with the bonding force increased by 25%.

[0089] Example 3

[0090] Surface treatment method of metal current-carrying bar: (1) pickling the metal current-carrying bar (made of copper and having a thickness of 0.027 mm) with 0.5% nitric acid for 10 min, then rinsing with distilled water and drying at 80° C. for 20 min;

[0091] (2) The cleaned and dried metal current-carrying strip is polished with sandpaper of 100 mesh, 400 mesh, 700 mesh and 1000 mesh in turn, and then polished with alumina polishing paste to obtain a treated metal current-carrying strip.

[0092] The SEM image of the untreated metal current carrying strip in Example 3 is as follows: Fig. 9 The measured surface roughness is shown in Fig.10 shown.

[0093] The SEM image of the metal current carrying strip after treatment in Example 3 is as follows: Fig.11 The measured surface roughness is shown in Fig.12 shown.

[0094] from Fig.10 and 12 It can be seen that the surface roughness of the untreated metal bus bar is 0.972 μm, and the surface roughness of the treated metal bus bar is 1.551 μm.

[0095] The same method was used to measure the bonding force of the untreated metal bus bar in Example 3 to be 84.14 gf, and the bonding force of the treated metal bus bar to be 107.23 gf, with the bonding force increased by 27%.

[0096] It can be seen from the above embodiments that after being processed by the method of the present invention, the surface roughness of the metal bus bar increases and the bonding force is improved.

[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A surface treatment method for a metal current-carrying bar, comprising: Plasma treatment, corona treatment or fine grinding is performed on the surface of the metal current-carrying bar to obtain a treated metal current-carrying bar; The power of the plasma treatment is 10 to 300 W, the time of the plasma treatment is 0.5 to 10 min, and the gas flow rate of the plasma treatment is 10 to 100 sccm; The voltage of the corona treatment is 5 to 15 kV, the time of the corona treatment is 5 to 60 s, and the current of the corona treatment is 10 to 50 mA; The fine grinding includes grinding with sandpaper, grinding paste or grinding with a diamond grinding tool.

2. The surface treatment method of a metal bus bar according to claim 1, characterized in that: The plasma source of the plasma treatment includes one or more of oxygen, argon and nitrogen.

3. The surface treatment method of a metal bus bar according to claim 1, characterized in that: The distance between electrodes in the corona treatment is 1 to 10 mm.

4. The surface treatment method of a metal bus bar according to claim 1, characterized in that: The sandpaper polishing is performed step by step by using sandpapers with different mesh sizes.

5. The surface treatment method of a metal bus bar according to claim 4, characterized in that: The mesh number of the sandpaper gradually increases during sanding.

6. The surface treatment method of a metal bus bar according to claim 4 or 5, characterized in that: The mesh number of the sandpaper during sanding is 100 to 1000 meshes.

7. The surface treatment method of a metal bus bar according to claim 6, characterized in that: The mesh difference between the sandpapers during sanding is 200 to 400 meshes.

8. The surface treatment method of a metal bus bar according to claim 1, characterized in that: The material of the metal current carrying bar includes copper, aluminum or nickel.

9. The surface treatment method of a metal bus bar according to claim 1, characterized in that: The thickness of the metal current-carrying bar is 0.01-0.1 mm.

10. The surface treatment method of a metal bus bar according to claim 1, characterized in that: The metal bus bar is cleaned and dried in sequence before use.